13, 14‐seco‐Withanolides from Physalis minima with Potential Anti‐inflammatory Activity. Issue 7 (2nd July 2016) - Lin, Ru; Guan, Yu‐Zhou; Li, Rui‐Jun; Xu, Xiao‐Ming; Luo, Jian‐Guang; Kong, Ling‐Yi
Abstract : Four new 13, 14‐ seco ‐withanolides, minisecolides A – D (1 – 4 ), together with three known analogues5 – 7, were isolated from the whole plants of Physalis minima . The structures of new compounds were determined on the basis of spectroscopic analysis, including 1 H‐, 13 C‐NMR, 2D‐NMR (HMBC, HSQC, ROESY), and HR‐ESI‐MS. Evaluation of all isolates for their inhibitory effects on nitric oxide (NO) production was conducted on lipopolysaccaride‐activated RAW264.7 macrophages. Compounds2, 3, 5, and6 showed inhibitory activities, especially for compound5 with IC 50 value of 3.87 μm . Abstract :